Step up. Revolution [videorecording (DVD)] - Speer, Scott, 1982-; Guzman, Ryan, 1987-; McCormick, Kathryn, 1990-; Coleman, Cleopatra, 1987-; Sims, Jamal; Zigman, Aaron (Summit Entertainment, LLC, 2012)
Emily arrives in Miami with aspirations of becoming a professional dancer and soon falls in love with Sean, a young man who leads a dance crew called 'The Mob'. When a wealthy businessman threatens to develop The Mob's historic neighborhood and displace thousands of people, they all work together to turn their performance art into protest art, and risk losing their dreams to fight for a greater cause.